(untitled) (Research Nepal Journal of Development Studies, 2019)
The study explores the changing gender relations in media as social development. Changing Gender Relations have been found expressed in the media that can be proven with different examples but the activists and campaigners of gender equality movement are found glued with the decade old metaphors till date. Though the biological identity of a person still determines the power but the gap has been narrowed down. Even men, as activists, have involved advocating for their gender based grievances created as a result of the patriarchy and masculinity. There is discrimination against women, and even violence against them is in the higher volume in the society, but the cases of the remedies have also increased. Power relations have been found very much gendered and sexist, but the account of changes has not been highlighted properly. Changes in power relations are seen in the media but recognition of the same is not made officially. A concept, that most of the women are victims because of their femininity and men are perpetrators because of their masculinity, has also been repeatedly expressed whereas it has been proved that masculinity does not have a biological basis. Methodologically the study is completely based on secondary information of literature review. In conclusion, a concept of social development lies in gender equality has been internalized at least preliminary level by the media that is needed to recognize by the society so that media will be more encouraged to make contributions for the issues of social development.